Towards an Integrated Model of Antecedents and Consequences of Perceived Risk of Investors in Tunisian Stock Market - Bejaoui, Azza; KARAA, Adel (Eastern Journal of Economics and Finance, 2015)
The study investigates the antecedents and consequences of the risk perceived by investors in the Tunisian Stock Market. In other words, it examines the factors affecting the perceived level of risk towards the stock market and the behavioral responses induced by the perception of risk. For this purpose, a questionnaire was developed and distributed to 411 individual investors chosen by 24 brokers’ firms present in the Tunis Stock Exchange. The results show that more the investor is optimistic and self-confident; the lower is the perceived level of risk towards the stock market. Similarly, a perception of a good quality of information disclosed as well as the satisfaction with yield re-allocation by listed companies, reduce the perceived risk towards the stock market. Nevertheless, the results prove that the existence of information asymmetry increases, instead of reducing risk perception. Moreover, perceiving risk towards the stock market leads to an intensive search for information (various types and sources of information), a good performance and a strong intention to reinvest. The use of structural equation model allowed us, on one hand, to report the importance of the risk perception in the decision- making process and on the other hand, to emphasise the role of partial mediator played by the investment performance between the risk perception and the intention of reinvestment.